Prevalence of anemia and factors affecting anemia among adolescent girls under field practice area of rural health training centre of western Maharashtra - Sonawane, Sangeeta V.; Todkar, Sampatti S.; Mulaje , Sanjay (International Journal Of Community Medicine And Public Health, 2024)
Background: India has the largest adolescents population in the world, 253 million, nearly 23 percent of India’s population. Adolescents anemia is severe public health problem in India, 59.1% by NFHS. As adolescent age is formative years for development, anemia at this stage of life has some long-term consequences, as maternal and foetal deaths. Methods: It was observational cross sectional study under field practice area of Rural Health Training Centre of Western Maharashtra. 350 adolescent girls were interviewed using predesigned, pretested questionnaire and their anemic status was assessed by hemoglobin estimation. Results were analyzed with the help of Microsoft Excel. Results: The prevalence of anemia in this study was found to be 64.8%. The prevalence of mild and moderate anemia among study participants was 29.4 and 35.4%, respectively. Mean age of study participants was 14.8±2.36 years. The majority 68.57% of girls were Hindu by religion and nuclear family (43.42%). Most of the girls belonged to socioeconomic class III (30%) followed by class IV (21%). A significant association was found between the prevalence of anemia with, educational status of mother, and status of attainment of menarche with excessive bleeding and not receiving iron folic acid tablets and girls had history of worm infestation (p<0.05). Conclusions: The prevalence of anemia among adolescent girls was very high, as compared to 59.1% by NFHS-5, which was higher in lower socio-economic strata and among those whose mothers were less educated and who attained menarche with excessive bleeding and not receiving iron folic acid tablets with history of worm infestation.